Inside Back Cover: Benchmarking the Stability of Oxygen Evolution Reaction Catalysts: The Importance of Monitoring Mass Losses (ChemElectroChem 12/2014). Issue 12 (2nd December 2014) - Frydendal, Rasmus; Paoli, Elisa A.; Knudsen, Brian P.; Wickman, Björn; Malacrida, Paolo; Stephens, Ifan E. L.; Chorkendorff, Ib
<x xml:space="preserve">Abstract</x> This cover picture highlights the importance of specifically quantifying the mass losses of oxygen evolving catalysts. By combining electrochemical measurements with inductively coupled plasma–mass spectrometry, significant dissolution processes occur, even though the catalysts show excellent performance in the short term, as shown on p. 2075.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>